Evolution of newborn screening in India and the way forward - Mukesh Darshan; Nitesh Kumar (Wolters Kluwer Medknow Publications, 2023)
Newborn screening (NBS) programs have gained recognition as successful initiatives in several developed countries. In India, the implementation of dried blood spot screening is slowly gaining traction, with both the private and public health-care sectors playing crucial roles. The objective of the study was to assess the evolution and current status of NBS programs in India and the contributions of the private and public sectors. The role of the private sector in NBS is explored, with private hospitals in urban areas offering screening options for parents willing to pay. The private facilities have better infrastructural facilities and technological capabilities as compared to government ones. We searched pubmed with the keywords NBS for metabolic disorders and inborn errors of metabolism, NBS in India and found out the relevant articles. Various public NBS programs in states such as Chandigarh, Goa, and Kerala are analyzed. The Chandigarh program, initiated in 2017, has emerged as a pioneering public NBS program in India, while Goa has implemented NBS programs in two phases, addressing shortcomings and focusing on follow-up and treatment resources. The Kerala program, initially a pilot, aims to screen every birth in government hospitals and expand to private hospitals. The Unique Methods of Management and Treatment of Inherited Disorders initiative by the Government of India and the Neonatal Early Evaluation Vision mission by the Delhi government are newer public sector initiatives targeting genetic disorders and metabolic error screening. The cost effectiveness of NBS program has been documented in low and middle income settings. With the major chunk of screening capabilities handled by private sector in Indian settings, it's imperative for funding and support for NBS in government settings. Achieving universal NBS in India may require time and concerted efforts; however, with improving health-care standards and financing mechanisms, there is optimism that NBS will find its routine and become a universally applied program.